Financial integration in the EU28 equity markets: Measures and drivers - Nardo Michela; Ossola Elisa; Papanagiotou Evangalia (Publications Office of the European Union, 2020)
We examine time-invariant and time-varying market integration across European stock markets. Market integration has been increasing especially during the crisis period. Among others, market capitalization, technological developments and overall political uncertainty drive financial integration and systematic volatility, while macroeconomic variables do not impact idiosyncratic volatility. High market integration is associated with decreasing diversification benefit. During crisis periods investors select portfolios that are not explained only by firm characteristics.
Keywords: F3; C23; 330; financial integration; equity markets; common factor approach; diversification benefits; drivers of integration